Simple correlated wavefunctions for the K-shell electrons of neutral atoms - Mitnik, Dario Marcelo (2005)
Simple correlated wavefunctions considering two K-shell active electrons of neutral atoms from He to Xe are presented in this paper, describing a variational method subject to a local Hartree potential representing the presence of outer shell electrons. Three kinds of electron–electron correlation functions have been studied with rigorous observation of the exact behaviour of the wavefunctions at the electron–electron and electron–nucleus coalescence points (Kato cusp conditions). Global properties, such as the energies and virial coefficients, as well as local properties, such as spatial mean values, together with scaling laws with the nuclear charge for the variational parameters, are also analysed. We calculated the expansion of the functions in terms of bipolar spherical harmonics. Finally, comparisons are made with a more rigorous, fully quantal close-coupling method, which also includes the same Hartree potential for the outer electrons.